Ethnic Identity and Suicide Risk among Hispanic/Latinx Young Adults: The Impact of Perceived Burdensomeness and Thwarted Belongingness. Issue 2 (3rd April 2021) - Oakey-Frost, Nicolas; Tucker, Raymond P.; Buckner, Julia D.
Abstract : Hispanic/Latinx college students experience SI/behaviors at high rates, yet there is a dearth of research on suicide risk and sociocultural correlates of suicide risk among Hispanic/Latinx individuals. This study examined the impact of ethnic identity on suicide risk among 63 Hispanic/Latinx young adults. Further, we tested a model in which ethnic identity is integrated into the Interpersonal Psychological Theory of Suicide Behavior (IPTS). Lower levels of ethnic identity attachment were related to greater suicide risk. Further, moderated mediation analyses indicated that perceived burdensomeness mediated the relation between ethnic identity and suicide risk at higher levels of thwarted belongingness. Findings highlight the importance of sociocultural factors in understanding the utility of the IPTS model among Hispanic/Latinx individuals.